2014
DOI: 10.1111/psyg.12095
|View full text |Cite
|
Sign up to set email alerts
|

The dementia diagnosis: a literature review of information, understanding, and attributions

Abstract: This review examines how people understand and make sense of a dementia diagnosis. The review explores how lay frameworks and information presented at diagnosis may inform a caregiver's understanding of dementia in a family member. Existing qualitative research exploring how caregivers understand and make sense of dementia is reviewed. A literature search was conducted, and the results indicated that family carers often receive little or unclear information about dementia, with diagnostic information often del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 64 publications
(154 reference statements)
0
34
0
Order By: Relevance
“…The most recent studies investigating information needs for persons with dementia and their caregivers reveal that these groups do not receive sufficient information, emphasizing a need to identify information that these groups require [11][12][13]. There is some evidence pointing to the need for information on management of the behavioural and psychological symptoms of dementia as well as information on legal and financial issues along the course of disease progression [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The most recent studies investigating information needs for persons with dementia and their caregivers reveal that these groups do not receive sufficient information, emphasizing a need to identify information that these groups require [11][12][13]. There is some evidence pointing to the need for information on management of the behavioural and psychological symptoms of dementia as well as information on legal and financial issues along the course of disease progression [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of PwD are cared for by their spouse or children at home (von Kutzleben, Schmid, Halek, Holle, & Bartholomeyczik, ; Stokes, Combes, & Stokes, ). Despite their close relation to PwD, family members who transition to the role of caregivers do not have sufficient preparation to fulfil the task (Ducharme, Levesque, Lachance, Kergoat, & Coulombe, ).…”
Section: Introductionmentioning
confidence: 99%
“…The need for information to educate and support non-professionals caring for people with dementia has been well documented in the dementia care literature (Chang et al 2010;Stajduhar et al 2011;Wackerbarth and Johnson 2002;Wald et al 2003), with some studies isolating specific communication gaps among professionals, patients and carers (Forbes, Bern-Klug, and Gessert 2000;Fried et al 2011;Keller et al 2008;Stokes, Combes, and Stokes 2015). A systematic review concluded that providing information for carers can reduce patients' neuropsychiatric symptoms and improve their quality of life (Corbett et al 2012).…”
Section: Research Contextmentioning
confidence: 99%